Credit Market Frictions and Sudden Stops - Yuko Imura (Bank of Canada, 2014)
Financial crises in emerging economies in the 1980s and 1990s often entailed abrupt declines in foreign capital inflows, improvements in trade balance, and large declines in output and total factor productivity (TFP). This paper develops a two-sector small open economy model wherein heterogeneous firms face collateralized credit constraints for investment loans. The model is calibrated using Mexican data, and explains the economic downturn and subsequent recoveries following financial crises. In response to a sudden tightening of credit availability, the model generates a large decline in external debt, an improvement in trade balance, and declines in output and TFP, consistent with the stylized facts of sudden stop episodes. Tighter borrowing constraints lead firms to reduce investment and production, which in turn results in some firms holding capital stock disproportionate to their productivity levels. This disrupts the optimal allocation of capital across firms, and generates an endogenous fall in measured TFP. Furthermore, the subsequent recovery is driven by the traded sector, since the credit crunch is more persistent among domestic financing sources relative to foreign financing sources. This is consistent with the experience of Mexico, where the relatively fast recovery from the 1994-95 crisis was driven mainly by the traded sector, which had access to international financial markets.
Keywords: E22; E32; F41; G01; 330; Business fluctuations and cycles; Credit and credit aggregates; Financial markets; International topics